The Conceptual Dilemma between Internal Control and Internal Audit in Egyptian Public Organizations - El- Sehetry, Gehan Mohammed Mahmoud; Ismael, Mamdouh Moustafa (The Arab Journal of Administration, 2025)
Purpose: This paper aims at determining the extent of the conceptual dilemma between internal control (IC) and internal audit (IA). It seeks to highlight to what extent the managers, internal auditors and external auditors in, Egyptian public organizations, distinguish between 1C and IA with respect to their concepts and function. Methodology: This paper seeks to present a conceptual model based on both analytical descriptive approach and statistical analysis. The analytical descriptive approach is used for explaining the perspectives related to the subject of the paper; whereas the statistical analysis is used, through a questionnaire, as a tool to collect data then analyze them to determine whether there is a confusion between IC and IA. Findings: The results revealed a confusion between IC and IA among the individuals participated in the experiment in the concepts and function which entailed the lack of clarity in defining the function of each. So, the study presents a theoretical framework that explains the concept and function of IC and IA in public organizations which contributes to defining the function and competencies of each. Originality/Value: This study provides a new contribution in studying the relationship between IC and IA. It can be regarded as a theoretical foundation for researchers to conducting empirical and comparative studies in the future. The study affords directive mechanisms to policy makers in order to enhance control, accountability procedures to achieve the efficiency and effectiveness in the Egyptian public organizations.